The Oppression Towards Black Female Character In Kindred Novel By Octavia E. Butler - Lufini, Andi Wardatul Jum’ah; Chasanah, Ida Nurul; Setijowati, Adi (Publikasi Indonesia, 2025)
This research explores the oppression experienced by the Black female protagonist in Octavia E. Butler's novel Kindred. Using qualitative methods and textual analysis, this paper examines how the character faces various forms of oppression as defined by Iris Marion Young’s theory: exploitation, marginalization, powerlessness, cultural imperialism, and violence. The findings reveal the deeply rooted systemic injustices within the context of slavery and its intergenerational trauma. This research contributes to understanding postcolonial feminism in speculative fiction narratives.